CBCT‐guided evolutive library for cervical adaptive IMRT. Issue 4 (15th March 2018) - Rigaud, Bastien; Simon, Antoine; Gobeli, Maxime; Lafond, Caroline; Leseur, Julie; Barateau, Anais; Jaksic, Nicolas; Castelli, Joël; Williaume, Danièle; Haigron, Pascal; De Crevoisier, Renaud
Abstract : Purpose: In the context of adaptive radiation therapy (ART) for locally advanced cervical carcinoma (LACC), this study proposed an original cone‐beam computed tomography (CBCT)‐guided "Evolutive library" and evaluated it against four other known radiotherapy (RT) strategies. Material and methods: For 20 patients who underwent intensity‐modulated radiation therapy (IMRT) for LACC, three planning CTs [with empty (EB), intermediate (IB), and full (FB) bladder volumes], a CT scan at 20 Gy and bi‐weekly CBCTs for 5 weeks were performed. Five RT strategies were simulated for each patient: "Standard RT" was based on one IB planning CT; "internal target volume (ITV)‐based RT" was an ITV built from the three planning CTs; "RT with one mid‐treatment replanning (MidTtReplan)" corresponded to the standard RT with a replanning at 20 Gy; "Pretreatment library ART" using a planning library based on the three planning CTs; and the "Evolutive library ART", which was the "Pretreatment library ART" strategy enriched by including some CBCT anatomies into the library when the daily clinical target volume (CTV) shape differed from the ones in the library. Two planning target volume (PTV) margins of 7 and 10 mm were evaluated. All the strategies were geometrically compared in terms of the percentage of coverage by the PTV, for the CTV and the organs at risk (OAR) delineated on the CBCT. Inadequate coverage of the CTV and OARs by the PTV was also assessed using deformable image registration. The cumulated dose distributions of each strategy were likewise estimated and compared for one patient. Results: The "Evolutive library ART" strategy involved a number of added CBCTs: 0 for 55%; 1 for 30%; 2 for 5%; and 3 for 10% of patients. Compared with the other four, this strategy provided the highest CTV geometric coverage by the PTV, with a mean (min–max) coverage of 98.5% (96.4–100) for 10 mm margins and 96.2% (93.0–99.7) for 7 mm margins ( P < 0.05). Moreover, this strategy significantly decreased the geometric coverage of the bowel. CTV undercoverage by PTV occurred in the anterior and superior uterine regions for all strategies. The dosimetric analysis at 7 mm similarly demonstrated that the "Evolutive library ART" increased the V42.75Gy of the CTV by 27%, 20%, 13%, and 28% compared with "Standard RT", "ITV‐based RT", "MidTtReplan", and "Pretreatment library ART", respectively. The dose to the bowel was also decreased by the "Evolutive library ART" compared with that by the other strategies. Conclusion: The "Evolutive library ART" is a personalized ART strategy that comprises a pretreatment planning library of three CT scans, enriched for half of the patients by one to three per‐treatment CBCTs. This original strategy increased both the CTV coverage and bowel sparing compared with all the other tested strategies and enables us to consider a PTV margin reduction.